Comparison of acute physiological responses between one long and two short sessions of moderate-intensity training in endurance athletes - Kjøsen Talsnes, Rune; Torvik, Per-Øyvind; Skovereng, Knut; Sandbakk, Øyvind (Frontiers in Physiology, 2024)
To compare acute physiological responses and perceived training stress between one long and two short time-and intensity-matched sessions of moderate-intensity training in endurance athletes.Methods: Fourteen male endurance athletes (VO2max: 69.2±4.2 mL•min -1 •kg -1 ) performed one 6x10min interval session (SINGLE) and two 3x10-min interval sessions interspersed with 6.5 h recovery (DOUBLE) of moderate-intensity training on two separate days, while running in the laboratory, using a counterbalanced cross-over trial. The two training days were separated into a 1 st part/session (interval stage 1-3) and 2 nd part/session (interval stage 4-6). Respiratory variables, heart rate (HR), blood lactate concentrations (BLa), and rating of perceived exertion (RPE) were collected during sessions, whereas supine heart rate (HR) was assessed in a 60-min recovery period following sessions. Measures of perceived training stress (1-10) were assessed in the morning of the subsequent day.Results: HR, Bla, and RPE increased in the 2 nd compared to 1 st part of SINGLE (168±7 vs. 173±7 bpm, 2.60±0.75 vs. 3.01±0.81 mmol•L -1 , and 13.4±1.0 vs. 14.8±1.1-point, respectively, all P<.05). HR and Bla decreased in the 2 nd compared to 1 st session of DOUBLE (171±9 vs. 166±9 bpm and 2.72±0.96 vs. 2.14±0.65 mmol•L -1 , respectively, both P<.05). SINGLE revealed higher supine HR in the recovery period following sessions (65.4±2.5 vs. 60.7±2.5 bpm P<.05), session RPE (sRPE, 7.0±1.0 vs. 6.0±1.3point, P=.001) and sRPE training load (929±112 vs. 743±98, P<.001) compared to DOUBLE. In the subsequent morning, increased levels of perceived fatigue and muscle soreness were observed following SINGLE compared to DOUBLE (7.0±2.5 vs. 8.0±1.0-point, P=.049 and 6.0±2.5 vs. 7.0±2.5point, P=.002, respectively).One long moderate-intensity training session was associated with a duration-dependent "drift" in physiological responses compared to two short time-and intensity-matched sessions, thereby suggesting a higher overall training stimulus. Simultaneously, the lower cost of the two shorter sessions indicates that such organization could allow more accumulated time at this intensity. Overall, these findings serve as a starting point to better understand the pros and cons of organizing moderateintensity training as one long versus shorter sessions performed more frequently (e.g. as "double threshold training") in endurance athletes.